VIGILANCE AND CONSUME: THE DISCIPLINE OF LEISURE IN SHOPPING MALLS: THE DISCIPLINE OF LEISURE IN SHOPPING MALLS (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This article intends to apprehend the relations that could be established among prisons, hospitals, quarters and factory with another environment more contemporary that has been proliferating in our time : the malls. Therefore we will use Michel Foucault’s analyze on disciplinary mechanisms developed in his work Watch and Punish. Unfolding the techniques pointed by the autor in the construction of docile bodies – the art of distribution; the control of activity; the organization of genesis; the composition of forces – as well as regarding the resources for good nurture – the hierarchical vigilance; the normalizing sanction; the exam – it is intended note the correlated mode that the malls are constituted. In addition this article will stand out the panoptism as a mechanism of control technologically developed in these specific spaces.